Features of effective goal shots by football players in games of high level teams - Pertsukhov, A.; Shalenko, V. (Slobozhanskyi herald of science and sport, 2020)
Purpose: to establish the peculiarities of effective goal shots by highly qualified football players. Material and Methods: registration of technical and tactical actions (TTA) was carried out using the games of the teams of 2019/2020 UEFA Champions League. In total, 108 games were analyzed. The following research methods were used in the article: analysis of scientific and methodological literature, registration of TTA, methods of mathematical statistics. Results: the paper presents data that characterize the features of effective goal shots by football players in the games of high-level teams. In total, 344 shots were recorded and analyzed in 108 games of the teams of 2019/2020 UEFA Champions League. All effective goal shots were classified according to the time, place, situation, method and conditions of performing. Conclusions: it was established that highly qualified football players were more likely to perform effective goal shots from 76 minute to 90 from the penalty area (except for goal area), after receiving the ball from a team partner, with the first touch, to kick the ball on the ground, to the lower part of a goal.